Excess Uric Acid Induces Gouty Nephropathy Through Crystal Formation: A Review of Recent Insights - Mei, Yongsheng; Dong, Bingzi; Geng, Zhuang; Xu, Lili (Frontiers in Endocrinology, 2022)
Uric acid (UA) is the final product of purine metabolism in the human body, and impaired purine metabolism can increase the uric acid in serum, finally resulting in hyperuricemia (HUA). Current evidences suggest that urates might have antioxidant properties under certain circumstances, but most evidences suggest that urates promote inflammation. Hyperuricemia leads to the formation of urate crystals, which might be recognized as a red flag by the immune system. Such a response stimulates macrophage activation, leads to the activation of NOD-like receptor protein 3 (NLRP3) inflammasome vesicles, and ultimately the production and liberation of interleukin-1b (IL-1b) and interleukin-18 (IL-18), which can mediate inflammation, apoptosis and necroinflammation and cause an inflammatory cascade response. The kidney is one of the most commonly affected organs in HUA, which promotes the development of chronic kidney disease (CKD) by damaging endothelial cells, activating the renin-angiotensin system (RAS), and promoting inflammatory responses. Pharmacological interventions and lifestyle modifications are the primary means for controlling gout and lowering UA. The febuxostat is safe for CKD patients in the UA lowering therapy. Although dialysis can reduce UA levels, the application of drug is also necessary for dialysis patients. This article reviews the synthesis and metabolism of UA, etiology of HUA, the relationship between HUA and kidney disease, the treatment of gout and gouty nephropathy (GN).